Standardized Process for Early Recognition and Treatment of Hypotension in Pediatric Oncology Patients Reduces Clinical Deterioration and Shock - Rutman, Lori (Pediatr Qual Saf, 2018)
INTRODUCTION: Pediatric oncology patients are a high-risk population for septic shock. These patients often screen positive for sepsis during hospitalization, making it difficult to discern when care escalations are warranted. This poses challenges to timely clinical decision-making, which can result in extended periods of hypotension and increased risk for clinical deterioration. The aim of this project was to decrease the frequency of “rescue events” (hypotension for 2 hours before initiation of vasoactive medications) in pediatric oncology patients by 25% within 6 months of implementing standardized hypotension [mean arterial pressure (MAP)] thresholds on a septic shock pathway. METHODS: A key driver diagram was developed (Fig. 1). Age-based MAP norms were integrated into the electronic medical record. Critical MAP thresholds for provider evaluation were included in a revised septic shock pathway. Rescue events were measured over time. RESULTS: The revised septic shock pathway was implemented in December 2016. Baseline data from 10/1/15 to 12/30/16 showed 10 rescue events (0.7 events per 1,000 patient days), with reduction to 2 rescue events from 1/1/17 to 6/30/17 (0.3 events per 1,000 patient days). This represents a 60% reduction in events, and 56% reduction in the rate of events. The distribution of days between rescue events shifted considerably after implementation (Fig. 2); median days between events increased from 16 days (interquartile range, 7–22) to 37 days (interquartile range, 27–56). CONCLUSION: Integration of simple, actionable blood pressure thresholds in a standardized pathway for sepsis led to a reduction of preventable harm (rescue events) among pediatric oncology patients.